Penyelesaian Konflik Perusahan Asuransi Terhadap Nasabah yang Meninggal Dunia dalam Persepektif Hukum Perdata - Saputra, Komang Agus Yoga; Sudiarawan, Kadek Agus (Indonesian Journal Publisher, 2024)
This research focuses on the resolution of conflicts between insurance companies and deceased policyholders from a civil law perspective. The problem formulation includes how these conflicts are resolved and analyzes the fairness of the resolution process for both parties. The aim of the study is to understand and analyze the procedures for resolving insurance disputes within the context of civil law, ensuring solutions that do not disadvantage either party. The research employs a scientific approach to empirical legal research. Insurance products generally offer similar protection, safeguarding policyholders from various risks. This protection includes death benefits and legal protection as outlined in